Systematic Review of the Socioeconomic Consequences in Patients With Multiple Sclerosis With Different Levels of Disability and Cognitive Function - Kavaliunas, Andrius; Danylaitė Karrenbauer, Virginija; Binzer, Stefanie; Hillert, Jan (Frontiers in Neurology, 2022)
Multiple sclerosis (MS) is a challenging and disabling condition, predominantly affecting individuals in early adulthood. MS affects both the physical, cognitive and mental health of persons suffering from the disease as well as having a great impact on their financial status and quality of life. However, there is a lack of systematic approach towards assessing socioeconomic consequences of MS. Our objective was to systematically review observational analytical studies investigating the socioeconomic consequences in persons with MS with different levels of physical disability and cognitive function. We conducted a systematic review on socioeconomic consequences of MS with a focus on employment-, income-, work ability-, and relationship-related outcomes in persons with MS with special focus on disability and cognition. Additionally, the educational characteristics were examined. From 4957 studies identified, 214 were assessed for eligibility and a total of 19 studies were included in this qualitative assessment; 21 different outcomes were identified. All identified studies reported higher unemployment, higher early retirement and higher risk of unemployment in relation to higher physical disability. Also, cognitive function was found to be a predictor of employment (unemployment). The studies pointed out significant correlations between greater disability and lower earnings and higher income from benefits. One study also found the same correlation in relation to cognitive function. The studies reported higher work disability in relation to higher physical disability and lower cognitive function. In conclusion, this systematic review summarizes the pronounced differences in various socioeconomic outcomes between MS patients with regards to their physical disability and cognitive function. We also identified a lack of studies with longitudinal design in this field that can provide more robust estimates with covariate adjustments such as disease modifying treatments.